Biochemical features of primary cells from a pediatric patient with a gain-of-function ODC1 genetic mutation. Issue 14 (24th July 2019) - Schultz, Chad R.; Bupp, Caleb P.; Rajasekaran, Surender; Bachmann, André S.
Abstract : We recently described a new autosomal dominant genetic disorder in a pediatric patient caused by a heterozygous de novo mutation in the ornithine decarboxylase 1 ( ODC1 ) gene. The new genetic disorder is characterized by global developmental delay, alopecia, overgrowth, and dysmorphic features. We hypothesized that this new mutation (c.1342 A>T) leads to a C-terminal truncation variant of the ODC protein that is resistant to normal proteasomal degradation, leading to putrescine accumulation in cells. ODC (E.C. 4.1.1.17) is a rate-limiting enzyme in the biosynthesis of polyamines (putrescine, spermidine, and spermine) that plays a crucial role during embryogenesis, organogenesis, and tumorigenesis. In this study, we show that primary dermal fibroblasts derived from a skin biopsy of a 3-year-old patient contain large amounts of ODC protein and putrescine compared with primary dermal (neonatal and adult) fibroblast control cells. Importantly, the accumulated ODC protein variant remained functionally active as we detected exceptionally high ODC enzyme activity in both primary dermal fibroblasts (12–17-fold of controls) and red blood cells (RBCs) (125–137-fold of controls), using a specific 14 C radioactive ODC activity assay. Exposure of primary dermal fibroblasts to ODC inhibitor α-difluoromethylornithine (DFMO) reduced the ODC activity and putrescine to levels observed in controls without adversely affecting cell morphology or inducing cell death. In conclusion, our patient and potentially other patients that carry a similar ODC1 gain-of-function mutation might benefit from treatment with DFMO, a drug with a good safety profile, to suppress the exceptionally high ODC activity and putrescine levels in the body.